Assessing psychological consequences following maxillofacial trauma using DASS scale – our experience - Pokharel, Prenit Kumar; Baliga, Mohan; Amirthraj, Anand; Mehar, Harpreet (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: The aim of the present study was to investigate the psychological consequences among hospitalized patients facing Maxillofacial trauma. Materials and Methods: Ninety-two patients (78 male and 14 female) following maxillofacial trauma were assessed initially and later again after 4-6 months of the injury. For assessment the Depression, Anxiety and Stress Scale (DASS) was used. Prevalence of Depression, Anxiety and Stress was assessed initially and later at follow-up in terms of percentage. Paired t-test was then used to assess if there is any significant difference in the pre and post assessment of Depression, Anxiety and Stress after maxillofacial trauma. Results: Of 92 patients, 41.3% had normal depression and 13%, 26%, 16.3% and 3.2% had mild, moderate, severe and extremely severe depression respectively in the initial assessment. Whereas in the follow up assessment, 37.8% were normal, 19.5 %, 31.7%, 10.9 % had mild, moderate, severe depression respectively and none had extremely severe depression. Similarly, of 92 patients 39.1 % of the subjects had normal anxiety, 6.5 %, 25 %, 15.2 % and 14.1 % had mild, moderate, severe anxiety and extremely severe anxiety respectively at the initial assessment. Whereas in the follow up assessment 45.1 % were normal, 12.1%, 28 %, 12.1% and 2.4 % had mild, moderate anxiety, severe and extremely severe anxiety respectively. Furthermore, of 92 patients, 79.3% of the subjects had normal stress, 8.7%, 10.8% and 1% had mild, moderate and severe stress respectively and no subjects had extremely severe stress at the initial assessment. During follow up assessment all patients were normal without any kind of stress. Paired t-test revealed that there was significant levels of anxiety in patients following maxillofacial trauma but no significant levels of Depression or Stress was found. Conclusion: Psychological morbidity commonly follows maxillofacial injury and it needs to be addressed in routine clinical practice. Asian Journal of Medical Sciences Vol.7(2) 2015 85-89